Gender Norm Conformity, Uncertainty, Communication, and Satisfaction Within Romantic Relationships: a Dyadic Model - (:unkn) unknown (My University, 2016)
Marital satisfaction is associated with better overall life satisfaction (Holt-Lunstad, Birmingham, & Jones, 2008) and myriad positive health outcomes (Beach & O’Leary, 1993; Kiecolt-Glaser & Newton, 2001). Sexual script theory suggests that within heterosexual romantic relationships, scripts are “the mechanism through which appropriate identities are made congruent with desired expectations” (Simon & Gagnon, 1984, p. 53). To examine how gender norm conformity within heterosexual relationships may be influenced by situational cues and to measure how norm conformity is related to interpersonal outcomes, I recruited 35 dyads for participation in a date description task and a questionnaire which measured gender norm conformity, relational uncertainty, relational communication, and relationship satisfaction. Multilevel modeling and the actor-partner interdependence model (APIM; Kenny, Kashy, & Cook, 2006) was used for analysis. The results of the study were mixed; there were no differences in gender norm conformity between primed dyads and non-primed dyads, and no significant partner effects were found. However, several significant actor effects were found. This study improves understanding of the relationship between gender norm conformity and interpersonal relationship outcomes by expanding the research on partner effects. These effects are useful for clinicians working with couples to improve relationship communication and satisfaction.
Keywords: Gender Norm; Interpersonal Communication; Relationship Satisfaction; Sexual Script Theory